Cognitive health promotion through a low-intensity high-volume webinar intervention for older adults at risk of future dementia - Keera N. Fishman; Keera N. Fishman; Christopher Pilieci; Linda Truong; Gillian Rowe; Renee Climans; Iris Yusupov Rose; Kelly J. Murphy; Kelly J. Murphy (Frontiers in Psychology)
IntroductionMild cognitive impairment (MCI) affects 1 in 10 older adults and is a significant risk factor for dementia, a condition impacting over 63 million people worldwide. Despite the growing need for dementia prevention care, resources to empower individuals with MCI/cognitive decline and their families remain limited. The Learning the Ropes Foundations© webinar was developed to provide a free, evidence-based, and accessible low-volume, high-intensity intervention to support brain health.MethodsBetween January and December 2024, 78 participants with cognitive decline (99% >60 years, 58% women) and 30 family members of those with cognitive decline (97% >50 years, 57% women) completed a survey assessing the webinar’s usability, satisfaction, and ability to motivate behavior change. One-month following webinar completion, 19 participants with cognitive decline completed a follow-up survey assessing their implementation of behavior changes. Surveys included Likert-scale and open-ended questions. Data were analyzed using descriptive statistics.ResultsAmong survey respondents, 82% of participants with cognitive decline and 97% of family agreed they could apply the information to their everyday lives, 81% of participants with cognitive decline and 100% of family agreed they would recommend the webinar, and 90% of all participants reported being motivated to adopt at least one behavior change. Of the one-month follow-up participants, 74% reported implementing at least one behavior change.DiscussionThe Learning the Ropes Foundations© webinar shows strong potential as a user-friendly resource that supports usability, satisfaction, and motivation for behavior change among individuals with MCI/cognitive decline and their families. Future directions include expanding reach and evaluating long-term lifestyle impacts.